2018
DOI: 10.1002/anie.201803052
|View full text |Cite
|
Sign up to set email alerts
|

Crowding Shifts the FMN Recognition Mechanism of Riboswitch Aptamer from Conformational Selection to Induced Fit

Abstract: In bacteria, the binding between the riboswitch aptamer domain and ligand is regulated by environmental cues, such as low Mg in macrophages during pathogenesis to ensure spatiotemporal expression of virulence genes. Binding was investigated between the flavin mononucleotide (FMN) riboswitch aptamer and its anionic ligand in the presence of molecular crowding agent without Mg ion, which mimics pathogenic conditions. Structural, kinetic, and thermodynamic analyses under the crowding revealed more dynamic conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…This dependence of the folding pathway on the relative timescales of ligand binding and conformational dynamics of the aptamer can be identified as a kinetic coupling mechanism occurring early in the decision tree of gene regulation (Figure 1B). Similar kinetic control mechanisms of ligand recognition by the aptamer have been observed to be operational in multiple other riboswitches (Manz et al, 2017;Rode et al, 2018;McCluskey et al, 2019;Sung and Nesbitt, 2019).…”
Section: Correlating the Timescales Of Ligand Binding To Rna Foldingsupporting
confidence: 53%
See 1 more Smart Citation
“…This dependence of the folding pathway on the relative timescales of ligand binding and conformational dynamics of the aptamer can be identified as a kinetic coupling mechanism occurring early in the decision tree of gene regulation (Figure 1B). Similar kinetic control mechanisms of ligand recognition by the aptamer have been observed to be operational in multiple other riboswitches (Manz et al, 2017;Rode et al, 2018;McCluskey et al, 2019;Sung and Nesbitt, 2019).…”
Section: Correlating the Timescales Of Ligand Binding To Rna Foldingsupporting
confidence: 53%
“…The transition between the IF and CS models is governed, on one hand, by the ligand concentration and, on the other hand, by temperature and cofactors affecting RNA folding such as the cationic micro-environment. Undoubtedly, evolutionary pressures shape the sequence composition of the riboswitch to finetune this balance to the cell's needs (Suddala and Walter, 2014;Suddala et al, 2015;Rode et al, 2018). Ligand recognition mechanisms like the CS and IF models have provided the basis for the kinetic selection of transcriptional riboswitches (Suddala and Walter, 2014).…”
Section: Riboswitches In Prokaryotes Allow For Tight Coupling Of Ligand Influx and Gene Expressionmentioning
confidence: 99%
“…Crowded and confined conditions can modify the structure and function of nucleic acids and proteins (96)(97)(98)(99)(100). High levels of molecular crowding have been shown to stabilize mutations in ribozymes (101), change the binding mechanism of a ligand to a riboswitch (102), and create a chaperoning effect to assist in aptamer folding (99). Ribozymes can also modify their environment (e.g., through cooperation (103)), presenting an attractive future target for mapping more complex fitness landscapes.…”
Section: Environment and The Fitness Landscapementioning
confidence: 99%
“…In addition to structural stabilization of the free state of single-stranded RNA, two competing mechanisms of target recognition have been reported in the presence vs absence of Mg 2+ . 66 Data from fluorescence titration, nuclease digestion, and isothermal titration calorimetry have suggested that without Mg 2+ , a flavin mononucleotide riboswitch interacts with its anionic target via an induced fit mechanism, where target recognition triggers conformational change. 66 Alternately, in the presence of Mg 2+ , this riboswitch undergoes a conformational selection mechanism, where RNA structural rearrangement precedes target binding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…66 Data from fluorescence titration, nuclease digestion, and isothermal titration calorimetry have suggested that without Mg 2+ , a flavin mononucleotide riboswitch interacts with its anionic target via an induced fit mechanism, where target recognition triggers conformational change. 66 Alternately, in the presence of Mg 2+ , this riboswitch undergoes a conformational selection mechanism, where RNA structural rearrangement precedes target binding. These two mechanisms occur via different conformational intermediates and with different binding rate constants.…”
Section: ■ Introductionmentioning
confidence: 99%